Thermal regime and heat transfer during the evolution of continental collision structures - Parphenuk O.I. (Федеральное государственное бюджетное учреждение науки Геофизический центр Российской академии наук, 2016)
The study of collision structures is conducted based on the complex model of the thermal and mechanical evolution of overthrusting process for the rheologically layered lithosphere, which includes brittle upper crust and the lower crust and lithospheric upper mantle with different effective viscosity values. Finite element models with Lagrangian approach were used for the problem simulation to study the real deformation and thermal history of orogen. Horizontal shortening leads to the upper crust overthrusting along the fault zone, additional loading to the lower layers which is redistributed in the process of uplift and erosion. This work concentrates on the thermal evolution of collision zones that formed due to upper crust overthrusting movement accompanied by ductile flows at the levels of the lower crust and the upper mantle. The major controls on thermal evolution of the regions with the thickened continental crust are the radiogenic heat supply within the crust, the thermal conductivity of the layers (including its anisotropy in the upper crust) and the rate and time scale of erosion. Calculations of different radiogenic heat content and thermal conductivity in the upper crust lead to the conclusions concerning the time and level of granite melt formation. The horizon of temperatures higher than wet granite solidus appears at the level of 30--40~km, moving upward to the depth 15--20~km at postcollisional stage. The range of maximum temperatures is presented based on the numerical modeling with reliable set of thermal parameters.
Keywords: COLLISION; OVERTHRUSTING; HEAT FLOW VALUE; GRANITE MELT; RADIOGENIC HEAT SOURCES; THERMAL CONDUCTIVITY